Adopsi Penggunaan Platform Crowdfunding untuk Donasi Amal pada Kalangan Muslim Milenial - Firdan Thoriq Faza; Astiwi Indriani (Universitas YARSI, 2021)
Nowdays fintech in the form of a crowdfunding is directed to help the problems of the economic needs of the community from ownership economy to sharing economy, so that individual financial problems can be resolved together. The study aims to analyze the factors that influence the millennial muslim to distribute charitable donations using crowdfunding. This study is a qualitative research with a case study method and the data analysis tool uses coding. The research data were generated from direct semi-structured interviews with the selection of respondents using purposive-sampling technique and Semarang city as the location. The results showed that there were five factors that influenced donors using crowdfunding, namely the donation process, donation affordability, donation flexibility, platform credibility and alternative payment schemes. The findings are an analysis of the results of the respondents' statements and experiences in donating using crowdfunding.